Mountains - Simon, Seymour (New York : Morrow Junior Books, 1994)
Introduces various mountain ranges, how they are formed and shaped, and how they affect vegetation, animals, and the human population.
Elem. School Library Collection.
Wilson's Children.
Wilson's Junior High School.
5.3
1-2
3-6
Keywords: Mountains -- Juvenile literature; Mountains; Mountains